2022
DOI: 10.3389/fendo.2022.832577
|View full text |Cite
|
Sign up to set email alerts
|

Serum Exosomes MicroRNAs Are Novel Non-Invasive Biomarkers of Intrahepatic Cholestasis of Pregnancy

Abstract: BackgroundIntrahepatic cholestasis of pregnancy (ICP) is closely related to the occurrence of adverse outcomes. Currently, total bile acids (TBAs) are the only diagnostic index for ICP, and its sensitivity and specificity have certain limitations. In this study, we aimed to develop potential biomarkers for the diagnosis of ICP.MethodsSixty pregnant women diagnosed with ICP and 48 healthy pregnant controls were enrolled in this study. We used the Agilent microRNA (miRNA) array followed by quantitative reverse t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 29 publications
0
0
0
Order By: Relevance
“…In another study, the researchers extracted exosomes from the serum of normal pregnant women and those with ICP and observed that t miR-4217, miR-1275, and miR-6891-5p expression in maternal serum exosomes was significantly lower in patients with ICP than in controls. Bioinformatics analysis revealed that the three exosomal miRNAs were primarily associated with the MAPK signaling pathway, which is closely associated with lipid metabolism (Dong et al, 2022). In conclusion, the miRNAs in serum and serum exosomes may act on lipid metabolism and the MAPK and AMPK signaling pathways, thereby inducing ICP onset.…”
Section: Mirnas and Lipid Metabolism And Mitogenactivated Protein Kin...mentioning
confidence: 88%
“…In another study, the researchers extracted exosomes from the serum of normal pregnant women and those with ICP and observed that t miR-4217, miR-1275, and miR-6891-5p expression in maternal serum exosomes was significantly lower in patients with ICP than in controls. Bioinformatics analysis revealed that the three exosomal miRNAs were primarily associated with the MAPK signaling pathway, which is closely associated with lipid metabolism (Dong et al, 2022). In conclusion, the miRNAs in serum and serum exosomes may act on lipid metabolism and the MAPK and AMPK signaling pathways, thereby inducing ICP onset.…”
Section: Mirnas and Lipid Metabolism And Mitogenactivated Protein Kin...mentioning
confidence: 88%